Bio-efficacy of Trichoderma spp. and its liquid culture filtrate on mycelial growth and management of onion black mould rot (Aspergillus niger Van Tieghem) in vitro and in vivo - R.K. PATIL, B.K. PRAJAPATI* and (Indian Phytopathology, 2017)
Black mould rot of onion incited by Aspergillus niger is an important post-harvest disease of onion under storage conditions and cause extensive losses. The present study was undertaken to assess the bio-efficacy of Trichoderma spp. and its culture filtrate in management of black mould rot in vitro and in vivo. Significantly lowest mycelial growth (19.00 mm) with highest mycelial growth inhibition was recorded in T. asperellum (78.89%) after 7th day of incubation in vitro. In vivo, pre-inoculation treatment with T. asperellum found significantly superior in reducing the black mould rot severity (0.00 and 0.06%) on 7th and 14th day after inoculation, respectively over control (21.67 and 29.33%). A similar trend was noted in post-inoculation treatment (0.16 and 0.33%) over control (23.00 and 29.67%). Significantly lowest mycelia growth (10.67 mm) with highest mycelial growth inhibition was recorded in liquid culture filtrate of T. harzianum (88.14%) over control. In vivo, pre-inoculation treatment with liquid culture filtrate of T. asperellum, T. harzianum and T. viride were found significantly superior showing no black mould rot severity on 7th and 14th day after inoculation over control (14.00 and 27.67%). In post-inoculation treatment T. asperellum, T. harzianum and T. viride were found significantly superior showing no black mould rot severity on 7th and on 14th day after inoculation over control (17.33 and 26.33%).